Imaging an aligned polyatomic molecule with laser-induced electron diffraction - Pullen, Michael G.; Wolter, Benjamin; Le, Anh-Thu; Baudisch, Matthias; Hemmer, Michaël; Senftleben, Arne; Schröter, Claus Dieter; Ullrich, Joachim; Moshammer, Robert; Lin, C. D.; Biegert, Jens (My University, 2015)
Laser-induced electron diffraction is an evolving tabletop method that aims to image ultrafast structural changes in gas-phase polyatomic molecules with sub-Ångström spatial and femtosecond temporal resolutions. Here we demonstrate the retrieval of multiple bond lengths from a polyatomic molecule by simultaneously measuring the C–C and C–H bond lengths in aligned acetylene. Our approach takes the method beyond the hitherto achieved imaging of simple diatomic molecules and is based on the combination of a 160 kHz mid-infrared few-cycle laser source with full three-dimensional electron–ion coincidence detection. Our technique provides an accessible and robust route towards imaging ultrafast processes in complex gas-phase molecules with atto- to femto-second temporal resolution.